(untitled) ("Journal "U". Economy. Management. Finance.", 2026)
This article analyzes the competition between cash and non-cash payments in Russia and globally, based on data from the Bank of Russia and Worldpay 2025. It examines factors driving consumer choice and the advantages and disadvantages of payment instruments. Particular attention is paid to the paradoxical growth in demand for cash in the context of digitalization and the prospects for implementing the Fast Payment System (SBP) and the digital ruble. The objective is to identify the key factors in choosing between cards and cash. Practical significance: these findings help consumers make informed payment choices, and banks adjust their strategies given the 43% of the population’s interest in cash.